How to spot hyper local news: comparison of news portal on facebook - Mior Kamarulbaid, Afiqah; Wan Abas, Wan Anita; Omar, Siti Zubaidah; Bidin, Rosmiza (International Journal of Modern Trends in Business Research (IJMTBR), 2019)
Coverage on local news may influence community beliefs about local issues and events. By employing framing theory, it helps to guide the researchers to explore and understand media patterns on framing headlines of hyperlocal news on Facebook in Malaysia. This study aims to explore and identify the framing pattern of hyperlocal news on Facebook pages. This is a comparison study between two hyperlocal news portals on Facebook. Data were gathered through content analyses of the portals’ Facebook pages. The study considered news reports (the whole article including headlines, number of likes and shares, and comments). By exploring and identifying the patterns of hyperlocal news on Facebook, it allows journalists and media organisations to see the popularity of local news and enable them to use the most relevant news to appeal to a focused audience in even smaller geographic areas.